Ecological recovery of an afro montane forest in southwestern Uganda - Lejju, J. B. (African Journal of Ecology, 2004)
A study of the regeneration of an afromontane forest was carried out in Mgahinga Gorilla National Park (MGNP), south-western Uganda. The area landscape has been subjected to agricultural encroachment for the last 50 years. The landscape was changed by terracing and removing the indigenous vegetation and replacing it with exotic tree species. Stratified random sampling was employed in sampling the vegetation. There was a significant difference in species richness and density in the three habitat types. The natural forest supported the highest stem density (75%) and the lowest stem density (4%) was recorded under exotic woodlots. Seedlings (<2 cm, diameter at breast height) accounted for the majority of juveniles in the three habitats. The natural forest had the highest density (24,625 seedlings ha)1) and exotic woodlots supported the lowest stem density (1350 seedlings ha)1)
Keywords: Cultivated area; Encroachment; Mgahinga; Recruitment; Woodlots